ChemInform Abstract: The Therapeutic Journey of Pyridazinone. Issue 47 (3rd November 2016) - Akhtar, Wasim; Shaquiquzzaman, M.; Akhter, Mymoona; Verma, Garima; Khan, Mohemmed Faraz; Alam, M. Mumtaz
Abstract: Review: 190 refs.